(untitled) (Docentes 2.0 Journal, 2023)
In the knowledge society, lifelong learning has become crucial for all professions, including teaching, due to the dizzying changes in production methods, labor relations, science, technology, and cultural diffusion. Since learning is a continuous process, teachers need to learn throughout their lives and are, therefore, constantly accompanied. In this sense, a study was conducted to inquire about the accompaniment and supervision received by teachers in Peruvian public schools. For this purpose, a humanistic approach was followed using a qualitative methodology through the inductive-deductive method, with a narrative design supported by the technique of documentary analysis of the literature selected in the SciELO, Latindex, LatinREV, and Google Scholar databases. The search was based on a series of previously established inclusion and exclusion criteria, which finally led to the selection of 15 scientific articles published in various scientific journals from 2019-2023. The results show the authors’ disinterest in a qualitative research approach to this educational practice. In conclusion, the Peruvian educational system should continue strengthening support and monitoring related to pedagogical practice, pedagogical reflection, learning achievement, and educational quality.